2011
DOI: 10.2139/ssrn.1911867
|View full text |Cite
|
Sign up to set email alerts
|

In-House Globalization: The Role of Globally Distributed Design and Product Architecture on Product Development Performance

Abstract: Changes in the global economy and technological advances are stimulating an increasing geographic distribution of new product design and development efforts. For large organizations that design and develop complex products, this geographic distribution has added a new layer of complexity to product development operations. In this empirical study of a large auto manufacturer, we examine the operational performance implications of splitting the design of vehicle subsystems across multiple geographic locations. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…(), Staats (), Handley and Benton (), and Gokpinar et al. (). In a finer grained analysis, Liker et al.…”
Section: Integration Challenges and Decisionsunclassified
See 1 more Smart Citation
“…(), Staats (), Handley and Benton (), and Gokpinar et al. (). In a finer grained analysis, Liker et al.…”
Section: Integration Challenges and Decisionsunclassified
“…For example, Gokpinar et al. () showed that centrality in product architecture amplifies the negative impact of global dispersion on subsystem outcomes. Langlois and Robertson () and Baldwin and Clark () argued that higher levels of modularity should be associated with higher rates of component innovation.…”
Section: Integration Challenges and Decisionsmentioning
confidence: 99%
“…In this space, two studies are related to our article. First, Gokpinar, Hopp, and Iravani () study coordination challenges that delay ECOs. In contrast, our focus is on the characterization of task uncertainty and the consequent implications for task flow management.…”
Section: Literature Review: Background and Contributionmentioning
confidence: 99%